2022
DOI: 10.1007/s12098-022-04394-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dengue: An Updated Review

Abstract: Dengue is an important public health problem with a wide clinical spectrum. The World Health Organization classifies dengue into probable dengue, dengue with warning signs, and severe dengue. Severe dengue, characterized by plasma leakage, severe bleeding, or organ impairment, entails significant morbidity and mortality if not treated timely. There are no definitive curative medications for dengue; management is supportive. Judicious fluid resuscitation during the critical phase of dengue is the cornerstone of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The qSOFA, comprising three vital signs directly associated with severe dengue, may account for its high speci city and NPV. Severe dengue, a critical manifestation of DF, is characterized by one or more of the following conditions: (1) signi cant plasma leakage leading to shock (known as dengue shock) and/or respiratory distress due to uid accumulation; (2) severe bleeding; and (3) pronounced organ impairment [14]. The persistence of vascular permeability and plasma leakage may progress to dengue shock syndrome, ranging from initial asymptomatic capillary leakage to compensated shock, hypotensive shock, and, ultimately, cardiac arrest [15].…”
Section: Discussionmentioning
confidence: 99%
“…The qSOFA, comprising three vital signs directly associated with severe dengue, may account for its high speci city and NPV. Severe dengue, a critical manifestation of DF, is characterized by one or more of the following conditions: (1) signi cant plasma leakage leading to shock (known as dengue shock) and/or respiratory distress due to uid accumulation; (2) severe bleeding; and (3) pronounced organ impairment [14]. The persistence of vascular permeability and plasma leakage may progress to dengue shock syndrome, ranging from initial asymptomatic capillary leakage to compensated shock, hypotensive shock, and, ultimately, cardiac arrest [15].…”
Section: Discussionmentioning
confidence: 99%
“…81 Based on this observation, it was concluded that these dengue patients might be protected because of the procoagulant effect of PMPs; thus, PMPs might play a role as a biomarker to determine prophylactic platelet transfusion. 82…”
Section: Corticosteroidsmentioning
confidence: 99%
“…The most dangerous manifestation that is seen in DENV infection is dengue shock syndrome (DSS), which results in a significant rise in vascular permeability. 72 Fluid resuscitation is crucial in severe dengue management. The primary goal of this therapy is to avert the complications associated with hypovolemic shock and vascular leakage.…”
Section: Management Of Denguementioning
confidence: 99%
See 2 more Smart Citations